2023
DOI: 10.1042/cs20220795
|View full text |Cite
|
Sign up to set email alerts
|

Novel pharmacological approaches in abdominal aortic aneurysm

Abstract: Abdominal aortic aneurysm (AAA) is a severe vascular disease and a major public health issue with an unmet medical need for therapy. This disease is featured by a progressive dilation of the abdominal aorta, boosted by atherosclerosis, ageing, and smoking as major risk factors. Aneurysm growth increases the risk of aortic rupture, a life-threatening emergency with high mortality rates. Despite the increasing progress in our knowledge about the etiopathology of AAA, an effective pharmacological treatment agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 278 publications
0
4
0
Order By: Relevance
“…, and AAA is positively related to vascular inflammatory infiltration. Nowadays, no proven pharmacological treatment is available to limit AAA formation and progression [ 51 ]. Maybe colchicine could not limit the growth of AAA eventually, our work indicated that colchicine played a protective role at the early stage of AAA formation, and further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…, and AAA is positively related to vascular inflammatory infiltration. Nowadays, no proven pharmacological treatment is available to limit AAA formation and progression [ 51 ]. Maybe colchicine could not limit the growth of AAA eventually, our work indicated that colchicine played a protective role at the early stage of AAA formation, and further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical management of patients with AAA is limited to surgical intervention of large aneurysms, a high-risk surgery with high healthcare costs. Unfortunately, no pharmacological strategies are currently available to limit disease progression and reduce the risk of aneurysm rupture; therefore, a deeper understanding of the pathophysiology of these diseases is essential to identify new therapeutic targets that improve patient care [62].…”
Section: Impact Of Pde4 On Vascular Aneurysm Developmentmentioning
confidence: 99%
“…Risk factors for AAA in diagnostic screening include hypertension, atherosclerosis, diabetes, etc, medications targeting these risk factors related diseases may help slow the progression of AAA, reducing the risk of rupture. In light of these information, the results of preclinical studies in animal models suggest that statins, antihypertensive drugs, doxycycline, metformin, and others have delaying effect on AAA progression ( 8 10 ). However, the three main AAA models currently available are elastase, CaCl2, and angiotensin II (AngII)/apolipoprotein E (AapoE)-deficient mouse models, each of which has defects that may not translate the findings to human AAA, and there is currently insufficient evidence from multiple clinical drug trials to conclusively prove the complete efficacy of these drugs in treatment ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%